2007
DOI: 10.1007/s00784-007-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells and alterations in collagen density: signs of periradicular herpesvirus infection?

Abstract: This study evaluated the presence and density of natural killer (NK) cells as well as collagen density in chronic apical periodontitis lesions and tried to find any correlations with concomitant herpesvirus infection or histopathological status of the lesion. Surgical specimens of chronic apical periodontitis lesions were surveyed for the presence and density of NK cells by immunohistochemical analysis. Collagen density in these lesions was quantified by means of histochemistry. All specimens were positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…No periapical lesion revealed cytomegalovirus‐positive B lymphocytes. As shown elsewhere (14), cytomegalovirus may also infect natural killer cells in periapical lesions.…”
Section: Cytomegalovirus‐positive Inflammatory Cells In 15 Periapicasupporting
confidence: 62%
“…No periapical lesion revealed cytomegalovirus‐positive B lymphocytes. As shown elsewhere (14), cytomegalovirus may also infect natural killer cells in periapical lesions.…”
Section: Cytomegalovirus‐positive Inflammatory Cells In 15 Periapicasupporting
confidence: 62%
“…For instance, Blom et al reported that tick-borne encephalitis virus-induced NK cell activation is primarily limited to differentiated CD57 + /CD56 dim+ NK cells [ 45 ]. Additionally, CD57 + NK cells are routinely implicated in herpesvirus infections [ 46 , 47 ]. Therefore, including this parameter may be of utility when establishing or ruling out an initial diagnosis of ME.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + /CD57 + T cells are considered senescent cells whose function is not fully understood, while in NK cells the acquisition of CD57 confers a greater cytotoxic potential to the cell. 2,10 In the present study, cells exhibiting immunostaining for CD57 associated with the cell morphology findings (large CD57 immunopositive cells with a cytoplasm containing several voluminous granules) were defined as NK cells. …”
Section: Discussionmentioning
confidence: 99%